2011
DOI: 10.1007/s00415-011-6093-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute transverse myelitis in demyelinating diseases among the Chinese

Abstract: The aim of the study was to characterize the demographic, clinical, and prognostic features of Chinese patients with acute transverse myelitis (ATM). The clinical data from ATM patients in a demyelinating disease database were analyzed retrospectively. Sixty-seven ATM patients with a follow-up duration longer than 2 years were identified. The frequency of neuromyelitis optica-related ATM (NMO-ATM) was high in our cohort (40.3%). Recurrent ATM (R-ATM), with a female predominance, was common in total idiopathic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 39 publications
4
18
0
Order By: Relevance
“…In a French study, Marignier and colleagues reported that there was no difference between NMOIgG sero-positive and sero-negative NMO patients according to their clinical, CSF, and imaging features 14 . However, in the Japanese, AQP4 antibody-positive NMO/OSMS patients had a greater frequency of longitudinally extensive spinal cord or brain lesions than did anti-AQP4 antibody-negative NMO/OSMS patients 9,[15][16][17] .…”
Section: Discussionmentioning
confidence: 98%
“…In a French study, Marignier and colleagues reported that there was no difference between NMOIgG sero-positive and sero-negative NMO patients according to their clinical, CSF, and imaging features 14 . However, in the Japanese, AQP4 antibody-positive NMO/OSMS patients had a greater frequency of longitudinally extensive spinal cord or brain lesions than did anti-AQP4 antibody-negative NMO/OSMS patients 9,[15][16][17] .…”
Section: Discussionmentioning
confidence: 98%
“…Transverse myelitis (TM) is an inflammatory demyelinating disorder of the spinal cord that has various manifestations [1]. TM has several subtypes according to origin but in China the most common are neuromyelitis optica (NMO) spectrum and multiple sclerosis (MS) [1].…”
Section: Introductionmentioning
confidence: 99%
“…TM has several subtypes according to origin but in China the most common are neuromyelitis optica (NMO) spectrum and multiple sclerosis (MS) [1].…”
Section: Introductionmentioning
confidence: 99%
“…TM has several subtypes according to origin but, in China, most of them are associated with neuromyelitisoptica (NMO) and multiple sclerosis (MS) [1]. However, the exact etiologies of inflammatory demyelinating TM are unclear and the details of their pathogenesis are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Transverse myelitis (TM) is an inflammatory demyelinating disorder of the spinal cord that has various manifestations [1]. TM has several subtypes according to origin but, in China, most of them are associated with neuromyelitisoptica (NMO) and multiple sclerosis (MS) [1].…”
Section: Introductionmentioning
confidence: 99%